Appointment and Conduction of Examinations: Legislative and Practical Problems - A. O. Naumova; M. S. Kucha (Bulletin of Kharkiv National University of Internal Affairs)
It has been noted that the problems of procedural guaranteeing of the rights of victims, suspects (accused) in terms of reforming the criminal procedural legislation are relevant during the appointment and holding of the examination and require further research.